WOOD QUALITY OF BIRCH (BETULA SPP.) TREES DAMAGED BY MOOSE - Härkönen, Sauli; Pulkkinen, Arto; Heräjärvi, Henrik (Lakehead University, 2009)
European white birch (Betula pubescens) and silver birch (B. pendula) are important tree species for Finnish pulp and wood-products industries. Moose (Alces alces) damage, however, reduces the quality of butt logs intended for high-quality plywood and saw logs. In addition to flaws in stem form, pith discoloration and color change outside the pith reduce quality and value of logs irrespective of their end use. Our objectives were to 1) analyze the external and internal quality of birch trees damaged by moose, 2) measure whether the severity, type, and occurrence of damage differedbetween silver birch and European white birch trees, and 3) evaluate visual criteria that would enable a forest-owner to assess damage and future value of moose-damaged birch trees prior to the first commercial thinning. We sampled 4 stands with a known history of moose damage; 18 trees per stand were classified by visual evaluation into 3 damage categories. The severity and type of damage lowering the internal quality of logs from sample trees were classified into 5 grades. The proportion of all visible color defects and/or decay was 74% in silver birch trees and 67% in white birch trees. Moose damage caused no visible color defect and/or decay in 35% of silver birch and 33% of white birch trees. The commercial quality and value of birch trees damaged by moose was reduced by the internal color defects and/or decay, even in certain trees without obvious external moose damage. Nevertheless, forest-owners can evaluate the internal quality of most birch trees in order to remove those of low-quality in the first commercial thinning by using external quality indicators of moose-damaged stems (e.g., stem form and clear curve at the point of stem breakage).